Answer with explanation:
The given statement is which we have to prove by the principal of Mathematical Induction
![2^(n)>n](https://img.qammunity.org/2020/formulas/mathematics/college/sprmwfbk283xr5j1lc22c0fqj7a5urjqmx.png)
1.→For, n=1
L H S =2
R H S=1
2>1
L H S> R H S
So,the Statement is true for , n=1.
2.⇒Let the statement is true for, n=k.
![2^(k)>k](https://img.qammunity.org/2020/formulas/mathematics/college/w2cexronaa2p7jb39wrmlxofbbrpx2tjvk.png)
---------------------------------------(1)
3⇒Now, we will prove that the mathematical statement is true for, n=k+1.
![\rightarrow 2^(k+1)>k+1\\\\L H S=\rightarrow 2^(k+1)=2^(k)* 2\\\\\text{Using 1}\\\\2^(k)>k\\\\\text{Multiplying both sides by 2}\\\\2^(k+1)>2k\\\\As, 2 k=k+k,\text{Which will be always greater than }k+1.\\\\\rightarrow 2 k>k+1\\\\\rightarrow2^(k+1)>k+1](https://img.qammunity.org/2020/formulas/mathematics/college/xu8t9ps97iz4mv6n0ot08ml6v7bp7msb1r.png)
Hence it is true for, n=k+1.
So,we have proved the statement with the help of mathematical Induction, which is
![2^(k)>k](https://img.qammunity.org/2020/formulas/mathematics/college/w2cexronaa2p7jb39wrmlxofbbrpx2tjvk.png)